A kind of perfluoro rubber sealing ring and preparation method thereof

By using polyurethane resin, inorganic nanofillers and modifiers in perfluoro rubber sealing rings, a highly crosslinked structure is formed, which solves the durability of perfluoro rubber under low temperature conditions and significantly extends the service life of the sealing ring. and sealing performance.

CN118580631BActive Publication Date: 2025-01-07GUANGZHOU JISU SEALING TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410604641.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-15
Publication Date
2025-01-07
Estimated Expiration
2044-05-15

AI Technical Summary

Technical Problem

Perfluoro rubber sealing rings have poor durability under low temperature conditions, resulting in a shortened service life in northern my country in winter and need to be replaced frequently.

Method used

Using a combination of perfluoroelastomer, polyurethane resin, inorganic nanofiller, crosslinking agent, accelerator, vulcanizing agent and modifier, improve material compatibility through maleic anhydride graft copolymer, silicone copolymer and dispersant and crosslinking degree, form a highly crosslinked three-dimensional network structure to enhance the low temperature resistance of the seal ring.

Benefits of technology

It significantly improves the service life and sealing performance of the sealing ring under -40℃ conditions, and extends the maintenance cycle of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005140015040000061
    Figure GDA0005140015040000061
Patent Text Reader

Abstract

The present application relates to the technical field of fluororubber sealing ring processing, and more specifically, to a perfluororubber sealing ring and a preparation method thereof, which is prepared from the following raw materials in parts by weight: 60-80 parts of perfluororubber, 20-30 parts of polyurethane resin, 20-40 parts of inorganic nanofiller, 3-5 parts of crosslinking agent, 1-2 parts of accelerator, 1-2 parts of vulcanizing agent and 4-9 parts of modifier, wherein each part of the modifier is prepared by mixing a maleic anhydride graft copolymer, a siloxane copolymer and a dispersant in a weight ratio of (4-5): (6-9): 5. The fluororubber sealing ring prepared by the above formula has good low temperature resistance and can be used for a long time under -40°C conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of fluororubber sealing ring processing, and more specifically, to a perfluororubber sealing ring and a preparation method thereof. Background Art

[0002] Perfluororubber, also known as perfluoroether rubber, is a polymer compound composed of a ternary copolymer of perfluoro(methyl vinyl) ether, tetrafluoroethylene and perfluoroolefin ether. After being prepared into a sealing ring, it has a good sealing effect.

[0003] The climate in northern my country is cold in winter, especially in the Northeast and other regions, where the temperature can reach -30℃ to -40℃. Outdoor equipment cannot keep warm well, resulting in leakage in many devices with sealing rings. Perfluororubber contains HF bonds, which makes the perfluororubber molecular chain more rigid, making it difficult to change its conformation under low temperature conditions, and its low temperature resistance is poor. Therefore, the service life of perfluororubber sealing rings will be greatly reduced when used in northern my country in winter, and they need to be replaced frequently, which is more troublesome. Summary of the invention

[0004] In order to improve the problem of poor low temperature resistance of perfluororubber, the present application provides a perfluororubber sealing ring and a preparation method thereof.

[0005] In the first aspect, the present application provides a perfluoro rubber sealing ring, which adopts the following technical solution:

[0006] A perfluoro rubber sealing ring is prepared from the following raw materials in parts by weight:

[0007] Perfluoro rubber 60-80 parts

[0008] Polyurethane resin 20-30 parts

[0009] Inorganic nanofiller 20-40 parts

[0010] 3-5 parts of crosslinking agent

[0011] 1-2 parts of accelerator

[0012] 1-2 parts of vulcanizing agent

[0013] Modifier 4-9 parts

[0014] Each portion of the modifier is prepared by mixing a maleic anhydride graft copolymer, a siloxane copolymer and a dispersant in a weight ratio of (4-5): (6-9): 5.

[0015] By adopting the above technical scheme, the prepared perfluororubber sealing ring has good low temperature resistance and can be used for a long time at -40°C. Polyurethane resin has good low temperature resistance, and when used with perfluororubber, it can effectively improve the low temperature resistance of the sealing ring. However, when perfluororubber and polyurethane resin are blended, due to the poor compatibility between the two, phase separation or interface instability may occur, affecting the low temperature resistance and sealing performance of the sealing ring. In the present application, the modifier is prepared by combining maleic anhydride grafted copolymer, siloxane copolymer and dispersant, which can effectively improve the compatibility between polyurethane resin and perfluororubber, ensure that the perfluoro sealing ring will not phase separate during processing or use, and can be used for a long time under low temperature conditions.

[0016] Among them, siloxane copolymers have a unique silicon-oxygen bond (Si-O) structure, which makes siloxane molecules have good flexibility and low surface energy. When siloxane copolymers are blended with perfluororubber, the silicon-oxygen bonds in the siloxane molecules can interact with the fluorine atoms in the perfluororubber molecules. This interaction may include van der Waals forces, hydrogen bonds, or dipole-dipole interactions. These interactions help to improve the compatibility of perfluororubber, so that perfluororubber and polyurethane resin are fully mixed and uniform, and a sealing ring with a stable structure is obtained, which can also maintain good sealing performance at a low temperature of -40°C; maleic anhydride grafted copolymers contain copolymers of maleic anhydride structural units, which usually have good reactivity and can react with perfluororubber and polyurethane trees to improve the compatibility of the two. The maleic anhydride grafted copolymer and the siloxane copolymer in the modifier work synergistically to improve the compatibility of perfluororubber and polyurethane resin, and promote the uniform dispersion and stable combination of the two during the blending process. Dispersants can improve the dispersion uniformity of various raw materials and improve the comprehensive properties of the sealing ring, such as low temperature resistance, tensile strength, and deformation resistance.

[0017] Inorganic nanofillers have a high specific surface area and excellent adsorption properties. They can fill into the tiny pores of the sealing ring to reduce the penetration of gas or liquid, thereby improving the sealing effect of the sealing ring. At the same time, they increase the tensile strength of the sealing ring under low temperature conditions and extend the service life of the sealing ring.

[0018] The synergistic effect of the accelerator and the vulcanizer allows the perfluororubber and the polyurethane resin to undergo a cross-linking reaction more quickly, forming a sealing ring with a stable structure and resistance to low temperatures.

[0019] The cross-linking agent can form a bridge between the perfluororubber and polyurethane resin molecules, forming a highly cross-linked three-dimensional network structure, thereby improving the low-temperature resistance of the sealing ring and extending the service life of the sealing ring under cold conditions.

[0020] Preferably, the maleic anhydride copolymer includes at least one of maleic anhydride grafted polyurethane, maleic anhydride grafted polyethylene, maleic anhydride grafted ethylene acrylate copolymer, ethylene-propylene-maleic anhydride copolymer, styrene-maleic anhydride copolymer and polypropylene-maleic anhydride graft.

[0021] Preferably, the siloxane copolymer includes at least one of a polydimethylsiloxane-polyether copolymer, a polydimethylsiloxane-polyester copolymer, a polydimethylsiloxane-polyacrylate copolymer and a polydimethylsiloxane-polyamide copolymer.

[0022] By adopting the above technical solution, the types of maleic anhydride copolymer and siloxane copolymer are optimized, the compatibility between perfluororubber and polyurethane resin is further improved, and the two are fully mixed and evenly obtained to obtain a sealing ring with a stable structure, which can maintain good sealing performance even at a low temperature of -40°C.

[0023] Preferably, the modifier is obtained by the following method:

[0024] The maleic anhydride graft copolymer, the siloxane copolymer and the dispersant are added into a twin-screw extruder according to weight, and extruded and granulated to obtain a modifier, and the extrusion temperature is 230-250°C.

[0025] Preferably, the inorganic nanofiller is a modified inorganic nanofiller, and the modified inorganic nanofiller is prepared by the following method:

[0026] A: Mix the inorganic nanofiller, silane coupling agent and solvent and stir for 1-2 hours to obtain a suspension;

[0027] B: Add epoxy resin oligomer to the suspension, heat to 80-90°C, add initiator, reflux heat, react for 5-8h, filter to obtain the primary product, centrifuge and wash the primary product, vacuum dry to obtain inorganic nanofiller.

[0028] Nanofillers can improve the sealing effect and tensile strength of the sealing ring and extend the service life of the sealing ring under low temperature conditions. However, the dispersibility of inorganic nanofillers in the perfluororubber system is poor, which affects the sealing effect of the sealing ring and under low temperature conditions. In view of this, the present application modifies the inorganic nanofillers so that the dispersibility of the inorganic nanofillers is greatly improved and can be evenly dispersed in the perfluororubber system.

[0029] In step A, the surface of the inorganic nanofiller is silanized by reacting the silane coupling agent with the inorganic nanofiller, and the silanized inorganic nanofiller reacts with the epoxy resin oligomer, so that the surface of the inorganic nanofiller is connected with the epoxy resin, thereby improving the dispersibility of the inorganic nanofiller. At the same time, since the surface of the inorganic nanofiller is connected with the epoxy resin, the bonding force between the nano inorganic filler and the perfluororubber can be improved, and the tensile strength and sealing performance of the sealing ring can be further improved.

[0030] Preferably, the weight parts of the raw materials used to prepare the modified inorganic nanofiller are as follows:

[0031] Inorganic nanofiller 20-40 parts

[0032] 30-40 parts of solvent

[0033] Silane coupling agent 7-12 parts

[0034] Epoxy resin oligomer 5-8 parts

[0035] Initiator 0.2-0.5 parts.

[0036] By adopting the above technical solution, the amount of raw materials used in preparing modified inorganic nanofillers is optimized, and the dispersibility of the inorganic nanofillers is further improved, so that the inorganic nanofillers can be evenly dispersed in the perfluororubber system.

[0037] Preferably, the inorganic nanofiller is a spherical inorganic nanofiller with an average particle size of 50-100 nm.

[0038] By adopting the above technical solution, more epoxy resin is connected to the surface of the inorganic nanofiller, thereby improving the dispersibility of the nanofiller and improving the bonding strength between the nano inorganic filler and the perfluororubber, so that the perfluororubber can still maintain good sealing properties under low temperature conditions.

[0039] Preferably, the degree of polymerization of the epoxy resin oligomer is 3-9.

[0040] Preferably, the epoxy resin oligomer includes at least one of glycidyl ether epoxy resin, glycidyl ester epoxy resin, alicyclic epoxy resin and aliphatic epoxy resin.

[0041] By adopting the above technical solution, the polymerization degree and type of epoxy resin are optimized, the bonding force between inorganic nanofiller and perfluororubber is further improved, and the low temperature resistance and sealing performance of the sealing ring are further improved.

[0042] Preferably, the silane coupling agent is at least one of γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane.

[0043] By adopting the above technical solution, the silanization efficiency of the inorganic nanofiller is improved, which is conducive to connecting more epoxy resins and improving the dispersibility of the nanofiller in the object.

[0044] In a second aspect, the present application provides a method for preparing a perfluororubber sealing ring, using the following technical solution:

[0045] A method for preparing a perfluororubber sealing ring comprises the following steps:

[0046] S1. According to parts by weight, perfluororubber and inorganic nanofiller are added to an open mill and mixed at a mixing temperature of 40-50° C. to obtain a mixture A;

[0047] S2, adding mixture A, polyurethane resin, crosslinking agent, accelerator, vulcanizing agent and modifier into an open mill for mixing at a mixing temperature of 40-70° C., and mixing evenly to obtain a mixed rubber;

[0048] S3, vulcanizing the rubber mix obtained in step S2 in a vulcanizer at a vulcanizing temperature of 150-200°C;

[0049] S4, placing the material after vulcanization in step S3 into a second stage of an oven for vulcanization at a vulcanization temperature of 200-270° C. to obtain a perfluororubber sealing ring.

[0050] By adopting the above technical solution, a perfluororubber sealing ring with good low temperature resistance is obtained, which can be used for a long time in an environment of -40°C. The above preparation method is simple, easy to operate, and suitable for mass production. In this application, the perfluororubber and the inorganic nanofiller are first mixed in order to increase the uniformity of the dispersion of the inorganic nanofiller in the system. The perfluororubber and the polyurethane resin can be fully cross-linked through two vulcanizations, thereby increasing the service life of the sealing ring under low temperature conditions.

[0051] Preferably, the first stage vulcanization time in step S3 is 10-15 minutes, and the second stage vulcanization time in step S4 is 4-12 hours.

[0052] By adopting the above technical solution, the first stage vulcanization time and the second stage vulcanization time are optimized, so that the perfluororubber and the polyurethane resin are fully cross-linked to form a sealing ring with a stable structure and resistance to low temperatures.

[0053] In summary, this application has the following beneficial effects:

[0054] 1. The present application prepares a perfluororubber sealing ring by mixing perfluororubber, polyurethane resin, inorganic nanofiller, crosslinking agent, lubricant, accelerator, vulcanizing agent and modifier, wherein the modifier is prepared by mixing maleic anhydride graft copolymer, siloxane copolymer and dispersant according to specific weight parts, and the compatibility of perfluororubber and polyurethane resin is improved by the action of the modifier. At the same time, under the action of the crosslinking agent, accelerator and vulcanizing agent, the perfluororubber and polyurethane resin form a highly crosslinked three-dimensional network structure, thereby improving the low temperature resistance of the sealing ring and extending the service life of the sealing ring under cold conditions.

[0055] 2. In the present application, the surface of the inorganic nanofiller is silanized by reacting the silane coupling agent with the inorganic nanofiller, and then the silanized inorganic nanofiller is reacted with the epoxy resin oligomer so that the inorganic nanofiller is connected to the epoxy resin, thereby improving the dispersibility of the nanofiller and improving the bonding strength between the nano inorganic filler and the perfluororubber, so that the perfluororubber can still maintain good sealing properties under low temperature conditions. DETAILED DESCRIPTION

[0056] Example

[0057] The raw materials in this application can be purchased commercially.

[0058] Example 1

[0059] A perfluororubber sealing ring is prepared by the following preparation method:

[0060] S1, adding 600g of perfluororubber and 200g of inorganic nanofiller (nanosilicon dioxide) into an open mill and mixing them at a mixing temperature of 40°C to obtain a mixture A;

[0061] S2, adding mixture A, 200 g of polyurethane resin, 30 g of crosslinking agent (tert-butyl peroxy-2-ethylhexyl carbonate), 10 g of accelerator (N-cyclohexyl-2-benzothiazolesulfenamide), 10 g of vulcanizing agent (trimercapto-s-triazine) and 50 g of modifier into an open mill for mixing at a mixing temperature of 40° C., and mixing uniformly to obtain a mixed rubber;

[0062] S3, vulcanizing the rubber compound obtained in step S2 in a vulcanizer at a vulcanizing temperature of 150° C. for 10 min;

[0063] S4, placing the material after vulcanization in step S3 into a second stage of an oven for vulcanization at a vulcanization temperature of 200° C. for a vulcanization time of 4 hours to obtain a perfluororubber sealing ring.

[0064] Perfluororubber was purchased from Wuhan Kemik Biopharmaceutical Technology Co., Ltd. The brand is Kemik and the grade is industrial grade.

[0065] The polyurethane resin was purchased from Dongguan Wanhe Plastic Raw Materials Co., Ltd., model number R198A-8.

[0066] The modifier is prepared by mixing 11 g of maleic anhydride grafted copolymer (maleic anhydride grafted polyurethane), 16 g of siloxane copolymer (polydimethylsiloxane-polyether copolymer) and 13 g of dispersant (sodium pyrophosphate) in a weight ratio of 4:6:5.

[0067] The maleic anhydride graft copolymer, the siloxane copolymer and the dispersant are added into a twin-screw extruder, extruded and granulated to obtain a modifier, and the extrusion temperature is 230°C.

[0068] Maleic anhydride grafted polyurethane was purchased from Dongguan Shenghao Plastic Raw Materials Co., Ltd., with an effective ingredient of 99.99%.

[0069] Polydimethylsiloxane-polyether copolymer was purchased from Guangzhou Wana Chemical Co., Ltd., model TEGO.

[0070] The difference between Example 2-3 and Example 1 is that the types, amounts and parameters of some raw materials for preparing the perfluororubber sealing ring are different. The specific differences are shown in Table 1:

[0071] Table 1 Types, amounts and parameters of raw materials for preparing perfluoro rubber sealing rings

[0072]

[0073]

[0074] In Example 2, the modifier is prepared by mixing 22 g of maleic anhydride grafted copolymer (maleic anhydride grafted polyethylene), 29 g of siloxane copolymer (polydimethylsiloxane-polyamide copolymer) and 18 g of dispersant (sodium dodecylbenzene sulfonate) in a weight ratio of 5:8:5.

[0075] Maleic anhydride grafted polyethylene was purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd. with the product number ZJ006.

[0076] Polydimethylsiloxane-polyamide copolymer was purchased from Hubei Langbowan Biopharmaceutical Co., Ltd. with a CAS number of 99904-16-2.

[0077] In Example 3, the modifier is prepared by mixing 24 g of maleic anhydride grafted copolymer (maleic anhydride grafted ethylene acrylate copolymer), 43 g of siloxane copolymer (polydimethylsiloxane-polyacrylate copolymer) and 24 g of dispersant (sodium lignin) in a weight ratio of 5:9:5.

[0078] Maleic anhydride grafted ethylene acrylate copolymer was purchased from Dongguan Sujia Polymer Raw Materials Co., Ltd. with the brand number 22E757.

[0079] Polydimethylsiloxane-polyacrylate copolymer was purchased from OnStar New Carbon Materials Changzhou Co., Ltd., PDMS is 9016-00-6 / 63148-62-9.

[0080] Example 4

[0081] A perfluororubber sealing ring. The difference between this embodiment and embodiment 1 is that the modifier is prepared by mixing 16g of maleic anhydride grafted copolymer (maleic anhydride grafted polyurethane), 11g of siloxane copolymer (polydimethylsiloxane-polyether copolymer) and 18g of dispersant (sodium pyrophosphate) in a weight ratio of 5:8:5.

[0082] Example 5

[0083] A perfluororubber sealing ring, the difference between this embodiment and embodiment 1 is that the inorganic nanofiller is a modified inorganic nanofiller, and the modified inorganic nanofiller is prepared by the following method:

[0084] A: Mix 200 g of inorganic nanofiller (spherical nanosilica, with an average particle size of 50 nm), 70 g of silane coupling agent (γ-aminopropyltriethoxysilane) and 300 g of solvent (acetone), and stir for 1 h to obtain a suspension;

[0085] B: Add 50 g of epoxy resin oligomer to the suspension, heat to 80°C, add 2 g of initiator (ammonium persulfate), reflux heat, react for 5 hours, filter to obtain the primary product, centrifuge and wash the primary product, vacuum dry to obtain an inorganic nanofiller.

[0086] The epoxy resin oligomer is a glycidyl ether epoxy resin with a polymerization degree of 3.

[0087] Example 6

[0088] A perfluororubber sealing ring, the difference between this embodiment and embodiment 1 is that the inorganic nanofiller is a modified inorganic nanofiller, and the modified inorganic nanofiller is prepared by the following method:

[0089] A: Mix 400 g of inorganic nanofiller (spherical nanosilica, with an average particle size of 100 nm), 120 g of silane coupling agent (N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane) and 400 g of solvent (toluene), and stir for 2 h to obtain a suspension;

[0090] B: Add 80 g of epoxy resin oligomer to the suspension, heat to 90°C, add 5 g of initiator (ammonium persulfate), reflux heat, react for 8 hours, filter to obtain the primary product, centrifuge and wash the primary product, vacuum dry to obtain an inorganic nanofiller.

[0091] Example 7

[0092] A perfluororubber sealing ring. The difference between this embodiment and embodiment 6 is that toluene is used instead of epoxy resin oligomer, and the types, amounts and experimental parameters of other raw materials are consistent with those of embodiment 6.

[0093] Example 8

[0094] A perfluororubber sealing ring. The difference between this embodiment and embodiment 6 is that toluene is used instead of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and the types, amounts and experimental parameters of other raw materials are consistent with those of embodiment 6.

[0095] Comparative Example

[0096] Comparative Example 1

[0097] A perfluororubber sealing ring. The difference between this comparative example and Example 1 is that ABS resin is used instead of polyurethane resin of equal mass, and the types, amounts and experimental parameters of other raw materials are consistent with those of Example 1.

[0098] ABS resin was purchased from Shanghai Changzheng Plastic Co., Ltd. with the brand name PA-757F.

[0099] Comparative Example 2

[0100] A perfluororubber sealing ring. The difference between this comparative example and Example 1 is that talcum powder is used to replace an equal amount of maleic anhydride graft copolymer, and the types, amounts and experimental parameters of other raw materials are consistent with those in Example 1.

[0101] Comparative Example 3

[0102] A perfluororubber sealing ring. The difference between this comparative example and Example 1 is that talcum powder is used to replace an equal amount of siloxane copolymer, and the types, amounts and experimental parameters of other raw materials are consistent with those of Example 1.

[0103] Comparative Example 4

[0104] A perfluororubber sealing ring. The difference between this comparative example and Example 1 is that 1,2-di(4-pyridyl)ethylene is used instead of the maleic anhydride graft copolymer, and the types, amounts and experimental parameters of other raw materials are consistent with those of Example 1.

[0105] Comparative Example 5

[0106] A perfluororubber sealing ring. The difference between this comparative example and Example 1 is that 1,2-di(4-pyridyl)ethylene is used instead of the siloxane copolymer, and the types, amounts and experimental parameters of other raw materials are consistent with those of Example 1.

[0107] Comparative Example 6

[0108] A perfluororubber sealing ring. The difference between this comparative example and Example 1 is that no dispersant is used, and the types, amounts and experimental parameters of other raw materials are consistent with those of Example 1.

[0109] Performance testing

[0110] The tensile strength and compression stress relaxation tests of the perfluororubber sealing rings prepared in Examples 1-8 and Comparative Examples 1-6 were performed.

[0111] Detection method / test method Tensile strength: According to the national recommended standard "GB / T528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", the tensile strength of the perfluororubber sealing ring is tested at a tensile speed of 500mm / min.

[0112] Sealing ring compression stress relaxation test: 1) According to the national recommended standard "GB / T 7759.1-2015 Determination of compression permanent deformation of vulcanized rubber or thermoplastic rubber Part 1: At room temperature and high temperature conditions", the sample is subjected to room temperature and high temperature compression permanent deformation test, with a compression amount of 15%, and compression at room temperature 23°C for 72h (expressed as 23°C×72h);

[0113] 1. According to the national recommended standard GB / T 7759.2-2014 Determination of compression set of vulcanized rubber or thermoplastic rubber Part 2: Under low temperature conditions, the sample was subjected to low temperature compression set test, with a compression amount of 15% and compression for 72h at low temperature of -40℃ (expressed as -40℃×72h). The experimental data are shown in Table 2:

[0114] Table 2 Experimental data of Examples 1-8 and Comparative Examples 1-6

[0115] Examples or Comparative Examples Tensile strength(MPa) Shrinkage stress relaxation (23℃) Shrinkage stress relaxation (-40℃) Example 1 16.5 5 10 Example 2 16.3 6 9 Example 3 16.6 6 10 Example 4 15.3 8 12 Example 5 17.6 4 7 Example 6 17.8 4 6 Example 7 16.4 6 10 Example 8 16.3 7 9 Comparative Example 1 12.3 12 30 Comparative Example 2 13.1 7 24 Comparative Example 3 14.3 8 20 Comparative Example 4 15.1 6 18 Comparative Example 5 14.6 6 15 Comparative Example 6 14.2 5 12

[0116] By comparing Example 1 with Comparative Example 1, the tensile strength of Comparative Example 1 is 12.3 MPa, the compression permanent deformation at 23°C is 12%, and the compression permanent deformation at -40°C is 30%; while the tensile strength of Example 1 is 16.5 MPa, the compression permanent deformation at 23°C is 5%, and the compression permanent deformation at -40°C is 10%; it can be seen that in the present application, by preparing the sealing ring with polyurethane resin, perfluororubber, modifier, inorganic nanofiller and other raw materials, the tensile strength of the sealing ring can be improved, and the service life of the sealing ring under low temperature conditions can be extended.

[0117] By comparing Example 1 with Comparative Example 2, the tensile strength in Comparative Example 2 is 13.1 MPa, the compression permanent deformation at 23°C is 7%, and the compression permanent deformation at -40°C is 24%. It can be seen that the tensile strength in Comparative Example 2 is reduced, and the compression permanent deformation at -40°C is increased by 17% relative to that at room temperature, which is much more than that in Example 1;

[0118] By comparing Example 1 with Comparative Example 3, the tensile strength in Comparative Example 3 is 14.3 MPa, the compression permanent deformation at 23°C is 8%, and the compression permanent deformation at -40°C is 20%. It can be seen that the tensile strength in Comparative Example 3 is reduced, and the compression permanent deformation at -40°C is increased by 12% relative to that at room temperature, which is much more than that in Example 1;

[0119] By comparing Example 1 with Comparative Example 4, the tensile strength in Comparative Example 4 is 15.1 MPa, the compression permanent deformation at 23°C is 6%, and the compression permanent deformation at -40°C is 18%. It can be seen that the tensile strength in Comparative Example 4 is reduced, and the compression permanent deformation at -40°C is increased by 12% relative to that at room temperature, which is much more than that in Example 1;

[0120] By comparing Example 1 with Comparative Example 5, the tensile strength in Comparative Example 5 is 14.6 MPa, the compression permanent deformation at 23°C is 6%, and the compression permanent deformation at -40°C is 15%. It can be seen that the tensile strength in Comparative Example 4 is reduced, and the compression permanent deformation at -40°C is increased by 9% relative to that at room temperature, which is much more than that in Example 1;

[0121] It can be seen from Example 1 and Comparative Examples 2-5 that by preparing the modifier together with the maleic anhydride graft copolymer and the siloxane copolymer, the tensile strength of the sealing ring can be further improved, and the service life of the sealing ring under low temperature conditions can be extended.

[0122] By comparing Example 1 with Comparative Example 6, the tensile strength in Comparative Example 6 is 14.2 MPa, the compression permanent deformation at 23°C is 5%, and the compression permanent deformation at -40°C is 12%. It can be seen that the tensile strength in Comparative Example 4 is reduced, and the compression permanent deformation at -40°C is increased by 7% relative to that at room temperature, which is much more than that in Example 1, indicating that by adding dispersibility to the modifier, the tensile strength of the sealing ring can be further improved, and the service life of the sealing ring under low temperature conditions can be extended.

[0123] By comparing Example 1 with Example 5-6, the tensile strength in Example 5-6 is increased, the compression permanent deformation at 23°C is less than that in Example 1, the compression permanent deformation at -40°C is less than that in Example 1, and the compression permanent deformation at -40°C changes little relative to the compression permanent deformation at room temperature. It can be seen that the use of the modified inorganic nanofiller of the present application can increase the service life of the sealing ring in a low temperature environment.

[0124] Comparing Example 6 with Example 7-8, the tensile strength in Example 7-8 is reduced, the compression permanent deformation at 23°C is less than that in Example 6, the compression permanent deformation at -40°C is less than that in Example 6, and the compression permanent deformation at -40°C changes greatly relative to the compression permanent deformation at room temperature, indicating that the modified inorganic nanofiller prepared by the preparation method of the present application can improve the service life and tensile strength of the sealing ring in a low temperature environment.

[0125] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A perfluoro rubber sealing ring, characterized in that: Prepared from the following raw materials in parts by weight: Perfluoro rubber 60-80 parts Polyurethane resin 20-30 parts 20-40 parts of modified inorganic nanofiller 3-5 parts of crosslinking agent 1-2 parts of accelerator 1-2 parts of vulcanizing agent Modifier 4-9 parts Each portion of the modifier is prepared by mixing a maleic anhydride graft copolymer, a siloxane copolymer and a dispersant in a weight ratio of (4-5): (6-9): 5; The siloxane copolymer includes at least one of a polydimethylsiloxane-polyether copolymer, a polydimethylsiloxane-polyester copolymer, a polydimethylsiloxane-polyacrylate copolymer and a polydimethylsiloxane-polyamide copolymer; The modified inorganic nanofiller is prepared by the following method: A: Mix the inorganic nanofiller, silane coupling agent and solvent and stir for 1-2 hours to obtain a suspension; B: Add epoxy resin oligomer to the suspension, heat to 80-90°C, add initiator, reflux heat, react for 5-8h, filter to obtain the initial product, centrifuge and wash the initial product, vacuum dry to obtain the modified inorganic nanofiller; The weight parts of the raw materials used to prepare the modified inorganic nanofiller are as follows: Inorganic nanofiller 20-40 parts 30-40 parts of solvent Silane coupling agent 7-12 parts Epoxy resin oligomer 5-8 parts Initiator 0.2-0.5 parts; The inorganic nano filler is spherical silicon dioxide with an average particle size of 50-100 nm.

2. A perfluororubber sealing ring according to claim 1, characterized in that: The maleic anhydride grafted copolymer includes at least one of maleic anhydride grafted polyurethane, maleic anhydride grafted polyethylene, maleic anhydride grafted ethylene acrylate copolymer and polypropylene-maleic anhydride graft.

3. A perfluororubber sealing ring according to claim 1, characterized in that: The polymerization degree of the epoxy resin oligomer is 3-9.

4. A perfluororubber sealing ring according to claim 1, characterized in that: The silane coupling agent is at least one of γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane.

5. A method for preparing a perfluororubber sealing ring as claimed in any one of claims 1 to 4, characterized in that: The method comprises the following preparation steps: S1. According to parts by weight, perfluororubber and inorganic nanofiller are added to an open mill and mixed at a mixing temperature of 40-50° C. to obtain a mixture A; S2, adding mixture A, polyurethane resin, crosslinking agent, accelerator, vulcanizing agent and modifier into an open mill for mixing at a mixing temperature of 40-70° C., and mixing evenly to obtain a mixed rubber; S3, vulcanizing the rubber mix obtained in step S2 in a vulcanizer at a vulcanizing temperature of 150-200°C; S4, placing the material after vulcanization in step S3 into a second stage of an oven for vulcanization at a vulcanization temperature of 200-270° C. to obtain a perfluororubber sealing ring.

6. The method for preparing a perfluororubber sealing ring according to claim 5, wherein: The first stage vulcanization time in step S3 is 10-15 minutes, and the second stage vulcanization time in step S4 is 4-12 hours.

Citation Information

Patent Citations

  • Weather-resistant solar cell backboard and preparation method thereof

    CN107304279A

  • Low-temperature-resistant rubber, preparation method thereof and air spring end cover applying low-temperature-resistant rubber

    CN114044986A